2022
DOI: 10.15252/embr.202153659
|View full text |Cite
|
Sign up to set email alerts
|

Bassoon controls synaptic vesicle release via regulation of presynaptic phosphorylation and cAMP

Abstract: Neuronal presynaptic terminals contain hundreds of neurotransmitter‐filled synaptic vesicles (SVs). The morphologically uniform SVs differ in their release competence segregating into functional pools that differentially contribute to neurotransmission. The presynaptic scaffold bassoon is required for neurotransmission, but the underlying molecular mechanisms are unknown. We report that glutamatergic synapses lacking bassoon feature decreased SV release competence and increased resting pool of SVs as assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…Bssn is an active‐zone protein involved in vesicular release that is essential for the formation of central synapses (Davydova et al, 2014; Gundelfinger et al, 2015; Montenegro‐Venegas et al, 2022). To get a closer insight into the functional state of perisomatic synaptogenesis, we counted active zones per soma (Bssn+ puncta) colocalizing with PV‐Tom terminals in GCs expressing SCR or shNL2 (Figure 4a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Bssn is an active‐zone protein involved in vesicular release that is essential for the formation of central synapses (Davydova et al, 2014; Gundelfinger et al, 2015; Montenegro‐Venegas et al, 2022). To get a closer insight into the functional state of perisomatic synaptogenesis, we counted active zones per soma (Bssn+ puncta) colocalizing with PV‐Tom terminals in GCs expressing SCR or shNL2 (Figure 4a,b).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that EGCG/AA NPs significantly increased the amplitude of evoked IPSCs in both METH group (151 ± 5.2% of baseline, p < 0.001) and saline group (148 ± 6.4% of baseline, p < 0.001), and there was no significant difference between the two groups in the magnitude of EGCG/AA NP‐induced potentiation of IPSCs ( p = 0.617; Figure 4A,B). EGCG has been proved to increase intracellular cAMP, 18 which facilitates neurotransmitter release through the activation of protein kinase A (PKA) at many synapses, both excitatory and inhibitory 19,20 . After treatment with PKA inhibitor H89 in METH and saline groups, we found that H89 prevented the effect of EGCG/AA NPs on IPSCs in METH ( p < 0.001) and saline ( p < 0.001) groups (Figure 4A,B).…”
Section: Resultsmentioning
confidence: 89%
“…EGCG has been proved to increase intracellular cAMP, 18 which facilitates neurotransmitter release through the activation of protein kinase A (PKA) at many synapses, both excitatory and inhibitory. 19,20 After treatment with PKA inhibitor H89 in METH and saline groups, we found that H89 prevented the effect of EGCG/AA NPs on IPSCs in METH ( p < 0.001) and saline ( p < 0.001) groups (Figure 4A,B). Taken together, EGCG/AA NPs treatments prevented the METH SA-induced reduction of GABAergic inhibition.…”
Section: Egcg/aa Nps Produced a Downward Shift In The Meth Dose-effec...mentioning
confidence: 92%
“…It is transiently unquenched upon contact with neutral pH of the extracellular solution, and is quenched again upon endocytosis and vesicular re-acidification, thereby allowing fast real-time assessment of SV recycling at individual synapses. We utilized an established field stimulation protocol [ 59 , 61 ] of 40 AP at 20 Hz to mobilize fusion of docked SVs corresponding to the readily releasable pool (RRP), followed by a train of 900 AP at 20 Hz in order to release SVs of the so-called recycling pool (RP). RRP and RP comprises of all release-competent SVs and signify the total recycling pool (TRP).…”
Section: Resultsmentioning
confidence: 99%
“…Sample size for all experiments was set according to previous publications, where the comparable parameters were assessed using the same methodology [ 52 , 61 ]. Statistical analyses were performed using Graphpad Prism 9 (GraphPad Software, San Diego, California, USA).…”
Section: Methodsmentioning
confidence: 99%